Proposal of convergence of e-Learning systems for t-Learning - Franco, B. B. [UNESP]; Oliveira, H. C. [UNESP]; Rodolpho, E. R. [UNESP] (My University, 2008)
This article presents considerations about viability on reutilize existing web based e-Learning systems on Interactive Digital TV environment according to Digital TV standard adopted in Brazil. Considering the popularity of Moodle system in academic and corporative area, such system was chosen as a foundation for a survey into its properties to create a specification of an Application Programming Interface (API) for convergence to t-Learning characteristics that demands efforts in interface design area due the fact that computer and TV concepts are totally different. This work aims to present studies concerning user interface design during two stages: survey and detail of functionalities from an e-Learning system and how to adapt them for the Interactive TV regarding usability context and Information Architecture concepts.
Keywords: e-Learning; Edutainment; Information architecture; Interactive TV; t-Learning; Digital TV; E-learning systems; Information architectures; Interactive digital TV; Interface designs; T-Learning; Two stage; User interface designs; Web based; Computer systems programming; Digital television; E-learning; Information retrieval; Information science; Knowledge management; Learning systems; Surveys; User interfaces; Application programming interfaces (API); Interactive television